Pengaruh Biaya Operasional Pendapatan Operasional (BOPO) Loan To Deposit Ratio (LDR) dan Non Performing Loan (NPL) terhadap Return On Assets (ROA) pada PT Bank Central Asia Tbk (BCA) Analis Periode 2019-2024 - Nur Aisyah; A. Rozi (ARZUSIN, 2026)
Research on banking financial performance continues to develop, but discussions that specifically examine the effects of Operating Expenses to Operating Income (BOPO), Loan to Deposit Ratio (LDR), and Non-Performing Loan (NPL) on Return on Assets (ROA) at PT Bank Central Asia Tbk still need to be strengthened. This study aims to analyze the effects of BOPO, LDR, and NPL on ROA. This study employed a quantitative approach with a causal-associative design. The research data consisted of secondary data obtained from the quarterly financial reports of PT Bank Central Asia Tbk for the 2019–2024 period, with 24 observations selected through the purposive sampling technique. Data were collected through documentation techniques and were then analyzed using multiple linear regression with the assistance of IBM SPSS. The results show that both partially and simultaneously, BOPO, LDR, and NPL have significant effects on ROA. These findings indicate that operational efficiency, credit distribution capability, and credit risk management are important factors in determining bank profitability. The conclusion of the study emphasizes the importance of controlling operating costs, optimizing credit distribution, and managing credit risk in improving banking financial performance. The implications of this study contribute to the development of banking finance studies and serve as practical considerations for bank management in formulating strategies to improve profitability.